Studi Ekonomis Implementasi Kapasitor Dengan Detuned Reactor Untuk Meningkatkan Efisiensi Faktor Daya - Wiharya, Chandra; Amaral, Hanifiyah Darna Fidya; Wiwaha, Sigit Setya; Prasetyo, Budi Eko (Elposys: Jurnal Sistem Kelistrikan, 2024)
The use of electrical energy plays a vital role in supporting the continuity of production processes in industrial environments. One critical area that heavily relies on electrical power supply is in the planning of installing a capacitor bank with a detuned reactor. The primary objective of this planning is to enhance the power factor (cos φ) from 60% to 85.2% during full-load operations and up to 94% when operating as per demand simulations. The evaluation of power quality from the implementation of the Capacitor with Detuned Reactor is conducted through simulations using ETAP 12.6.0 software.The simulation results from ETAP 12.6.0 produce comparative graphs between buses equipped with the Capacitor with Detuned Reactor and buses without it, both during full-load operational conditions and when only operating in simulations. The information derived from the simulation provides a deeper insight into the impact of installing the capacitor with detuned reactor on power factor and power quality within this industrial environment. With this understanding, further steps can be taken to optimize the electrical power system within the industrial setting.